Mitochondrial N-formyl methionine peptides contribute to exaggerated neutrophil activation in patients with COVID-19 - Runa Kuley; Bhargavi Duvvuri; Jeffrey J. Wallin; Nam Bui; Mary Vic Adona; Nicholas G. O’Connor; Sharon K. Sahi; Ian B. Stanaway; Mark M. Wurfel; Eric D. Morrell; W. Conrad Liles; Pavan K. Bhatraju; et al. (Virulence, 2023)
Neutrophil dysregulation is well established in COVID-19. However, factors contributing to neutrophil activation in COVID-19 are not clear. We assessed if N-formyl methionine (fMet) contributes to neutrophil activation in COVID-19. Elevated levels of calprotectin, neutrophil extracellular traps (NETs) and fMet were observed in COVID-19 patients (n = 68), particularly in critically ill patients, as compared to HC (n = 19, p < 0.0001). Of note, the levels of NETs were higher in ICU patients with COVID-19 than in ICU patients without COVID-19 (p < 0.05), suggesting a prominent contribution of NETs in COVID-19. Additionally, plasma from COVID-19 patients with mild and moderate/severe symptoms induced in vitro neutrophil activation through fMet/FPR1 (formyl peptide receptor-1) dependent mechanisms (p < 0.0001). fMet levels correlated with calprotectin levels validating fMet-mediated neutrophil activation in COVID-19 patients (r = 0.60, p = 0.0007). Our data indicate that fMet is an important factor contributing to neutrophil activation in COVID-19 disease and may represent a potential target for therapeutic intervention.